The perception of the modern financial instruments by the classical investors - AlTabreezi, Ghadeer (Afyon Kocatepe Üniversitesi Sosyal Bilimler Enstitüsü)
This study investigates classical investors' perceptions of modern financial instruments in Saudi Arabia, focusing specifically on exchange-traded funds (ETFs), derivatives, real estate investment trusts (REITs), and cryptocurrencies. Employing a mixed-methods research design, both qualitative and quantitative data were collected through structured questionnaires distributed among Saudi classical investors, traditionally inclined towards tangible assets and fixed-income investments due to cultural preferences and risk aversion. The analysis highlights how behavioral finance factors—including overconfidence, disposition effect, blue-chip bias, and herding—affect investor perceptions and decision-making processes. Additionally, the research explores the critical role of financial literacy in shaping attitudes toward modern financial products. Findings indicate that limited financial literacy and strong cognitive biases present significant barriers to adopting new financial instruments. This study recommends targeted financial education initiatives and strategic policy adjustments to enhance investors' understanding and acceptance of innovative financial products, aligning with the objectives of Saudi Arabia’s Vision 2030.

Bu çalışma, Suudi Arabistan'daki klasik yatırımcıların modern finansal araçlara ilişkin algılarını, özellikle borsa yatırım fonları (ETF'ler), türevler, gayrimenkul yatırım ortaklıkları (GYO'lar) ve kripto para birimlerine odaklanarak araştırmaktadır. Karma yöntemli bir araştırma tasarımı kullanılarak, kültürel tercihler ve riskten kaçınma nedeniyle geleneksel olarak maddi varlıklara ve sabit gelirli yatırımlara eğilimli olan Suudi klasik yatırımcıları arasında dağıtılan yapılandırılmış anketler aracılığıyla hem nitel hem de nicel veriler toplanmıştır. Analiz, aşırı güven, eğilim etkisi, üst düzey yatırımcı önyargısı ve sürü gibi davranışsal finans faktörlerinin yatırımcı algılarını ve karar alma süreçlerini nasıl etkilediğini vurgulamaktadır. Ek olarak, araştırma, modern finansal ürünlere yönelik tutumları şekillendirmede finansal okuryazarlığın kritik rolünü araştırmaktadır. Bulgular, sınırlı finansal okuryazarlığın ve güçlü bilişsel önyargıların yeni finansal araçları benimsemede önemli engeller oluşturduğunu göstermektedir. Bu çalışma, Suudi Arabistan'ın Vizyon 2030 hedeflerine uygun olarak yatırımcıların yenilikçi finansal ürünleri anlama ve kabul etmelerini artırmak için hedefli finansal eğitim girişimleri ve stratejik politika ayarlamaları önermektedir.
Klasik yatırımcıların modern finansal enstrümanları algılayışı
Keywords: Classical Investors; Modern Financial Instrument; Behavioral Finance; Financial Literacy; Klasik Yatırımcılar; Modern Finansal Araçlar; Davranışsal Finans; Finansal Okuryazarlık